De novo 11q13.3q13.4 deletion in a patient with Fanconi renotubular syndrome and intellectual disability: Case report and review of literature - Shen, Yingxiao; Xu, Xiaoqin; Chen, Jiansong; Wang, Jingjing; Dong, Guanping; Huang, Ke; Fu, Junfen; Wu, Dingwen; Wu, Wei (Frontiers in Pediatrics, 2023)
Objective: To explore the genetic etiology of a child with dysmorphic face, developmental delay, mental retardation, Fanconi renotubular syndrome, Chiari malformations. Materials and Methods: Whole exome sequencing (WES), Copy number variation sequencing (CNV-seq), and mitochondrial gene detection (Long-PCR+NGS) were applied to detect possible pathogenic mutations and chromosomal copy number variations (CNVs), together with databases and literature reviews to clarify the pathological significance of the candidate mutations. Results: The WES revealed a 2.10 Mb interstitial deletion from 11q13.3 to 11q13.4, which was later confirmed by CNV-seq, involving 11 OMIM genes, among which SHANK2, DHCR7, NADSYN1, FADD, NUMA1, IL18BP, ANO1, and FGF3 are disease-causing. Mitochondrial gene shows no variations. Conclusion: The child has carried a de novo 11q13.3q13.4 microdeletion, in which SHANK2 genes may be the key gene responsible for phenotype of mental retardation. The renal manifestation of the child, which can be diagnosed as Fanconi renotubular syndrome, has an unknown cause but may be resulted from the effect of ANO1 gene. This case adds a new phenotype to the deletion of this region.